Development and Validation of a Self-reported Questionnaire for Measuring Internet Search Dependence - Wang, Yifan; Wu, Lingdan; Zhou, Hongli; Xu, Jiaojing; Dong, Guangheng (Frontiers in Public Health, 2016)
Internet search has become the most common way that people deal with issues and problems in everyday life. The wide use of Internet search has largely changed the way people search for and store information. There is a growing interest in the impact of Internet search on users’ affect, cognition, and behavior. Thus, it is essential to develop a tool to measure the changes in psychological characteristics as a result of long-term use of Internet search. The aim of this study is to develop a Questionnaire on Internet Search Dependence (QISD) and test its reliability and validity. We first proposed a preliminary structure and items of the QISD based on literature review, supplemental investigations, and interviews. And then, we assessed the psychometric properties and explored the factor structure of the initial version via exploratory factor analysis (EFA). The EFA results indicated that four dimensions of the QISD were very reliable, i.e., habitual use of Internet search, withdrawal reaction, Internet search trust, and external storage under Internet search. Finally, we tested the factor solution obtained from EFA through confirmatory factor analysis (CFA). The results of CFA confirmed that the four dimensions model fits the data well. In all, this study suggests that the 12-item QISD is of high reliability and validity and can serve as a preliminary tool to measure the features of Internet search dependence.